Comparison of quadriceps femoris properties, surface electromyography parameters and foot posture asymmetries between patients with unilateral and bilateral knee osteoarthritis - Shen, Xingxing; Tian, Jiaqing; Chen, Jiahao; Zhang, Jiahao; Cheng, Sirun; Xiang, Ruian; Xu, Xuemeng (Frontiers in Physiology, 2025)
ObjectiveTo investigate the differences in quadriceps femoris (QF) properties, surface electromyography (sEMG) parameters and foot posture asymmetries between patients with unilateral and bilateral knee osteoarthritis (KOA), and to analyze the factors related to foot posture asymmetry.MethodsA total of 32 patients with unilateral KOA (unilateral group, UG) and 35 patients with bilateral KOA (bilateral group, BG) were enrolled in this study. The severity of knee osteoarthritis symptoms was assessed, and the affected legs were categorized as relatively severe leg (RSL) or relatively moderate leg (RML) based on the Visual Analogue Scale (VAS). Surface electromyography was utilized to measure the root mean square (RMS) values of rectus femoris (RF), vastus medialis (VM), and vastus lateralis (VL) during a straight leg raise task. Biomechanical characteristics, including muscle tone and stiffness, were measured using MyotonPRO. The foot posture index-6 (FPI-6) was applied to assess foot posture and asymmetrical foot posture scores. Additionally, we calculated the asymmetry indices of muscle tone (AsyTone), stiffness (AsyStiffness), and root mean square (AsyRMS) for the QF, along with their FPI asymmetry scores.ResultIn the evaluation of RF, VM, and VL in both groups, the RMS on the RML was significantly higher than that on the RSL (P < 0.05), while muscle tone and stiffness on the RSL were significantly higher than those of the RML (P < 0.05). In UG, AsyTone (RF), AsyTone (VM), AsyStiffness (RF), AsyStiffness (VM), AsyStiffness (VL) and AsyRMS (VM) were significantly higher than those in BG (P < 0.05). AsyTone (VL) was significantly lower than that in BG (P < 0.01). There was no significant difference in AsyRMS (RF) and AsyRMS (VL) between the two groups (P > 0.05). Regarding the FPI asymmetry scores, the proportion of asymmetry (including asymmetry and severe asymmetry) in the UG (65.6%) was much more frequent compared with that of BG (34.3%), with a statistically significant difference (χ2 = 6.57, P = 0.01). Furthermore, the VAS score and K/L grade were significantly correlated with the FPI asymmetric score in the UG (b = 1.065; 95% CI: 0.194, 1.936; p = 0.019 and b = 1.770; 95% CI: 0.215, 3.325; p = 0.028, respectively) and BG (b = 0.665; 95% CI: 0.117, 1.212; p = 0.020 and b = 1.523; 95% CI: 0.414, 2.632; p = 0.009, respectively).ConclusionBoth unilateral and bilateral patients with KOA exhibited a propensity for asymmetry in the properties of the QF, RMS values, and foot postures on both sides. Notably, unilateral patients tended to demonstrate this asymmetry more prominently and exhibit a higher prevalence of foot posture asymmetry compared to those bilateral patients. Furthermore, the degree of foot posture asymmetry was closely linked to pain severity and K/L grading whether in unilateral or bilateral KOA patients.